Wearable activity trackers for promoting physical activity : a systematic meta-analytic review - Li, Caining (2021)
Purpose: Although wearable activity trackers hold a promise of nudging people toward a more active lifestyle, current research reveals inconsistent findings regarding their effectiveness. The objectives of this paper are two-fold: (1) to synthesize evidence on the effects of wearable activity trackers for improving physical activities, and (2) to identify potential moderators of effect size. Methods: A systematic meta-analytic review was conducted. Forty-eight eligible papers based on forty-four distinct trials were identified through a systematic literature search process. Two authors independently extracted information from each study based on predefined data fields. Random-effects meta-analysis, subgroup analysis, and meta-regression analysis were employed. Results: First, interventions with wearable activity trackers significantly increased daily steps and weekly moderate-to-vigorous physical activity but had no impact on light physical activity or sedentary behavior. Second, daily steps and weekly moderate-to-vigorous physical activity were associated with participants’ characteristics (i.e., gender, age, medical condition, and baseline physical activity level) and intervention features (i.e., sensors, modes of expert support, and intervention duration). The identified factors explained 53% of the total variance for weekly moderate-to-vigorous physical activity. Conclusions: The use of wearable activity trackers effectively improves conscious exercise behavior, including daily steps and weekly moderate-to-vigorous physical activity, but not effective for modifying habitual behavior, such as light physical activity and sedentary behavior. We also explicitly show that the extent to which the interventions with wearable activity trackers help users is contingent on the type of users and the design and delivery of interventions. Future studies are called to validate the findings and to offer theoretical explanations.